2019
DOI: 10.1002/dmrr.3187
|View full text |Cite
|
Sign up to set email alerts
|

Milk in the prevention and management of type 2 diabetes: The potential role of milk proteins

Abstract: Globally, diabetes mellitus is not only considered a leading cause of mortality and morbidities but has also created a substantial economic burden. There is growing evidence that foods and their components can be implemented in the prevention and management of type 2 diabetes mellitus (T2DM). Increased dairy consumption has been linked to a lower risk of T2DM. The protective role of dairy foods in the development of T2DM is thought to be largely attributable to dairy nutrients, one of them being dairy protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 140 publications
0
23
0
3
Order By: Relevance
“…The inverse association between milk or dairy product consumption and the metabolic syndrome may be collectively or individually mediated by specific nutrients within milk and dairy products. There is emerging evidence that milk protein may have the potential to improve body composition (58) , glucose metabolism (59) and lipid profile (3) . Milk protein and its derived peptides have been shown to reduce blood pressure, possibly via inhibition of angiotensin I-converting enzyme (4,60) .…”
Section: Potential Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inverse association between milk or dairy product consumption and the metabolic syndrome may be collectively or individually mediated by specific nutrients within milk and dairy products. There is emerging evidence that milk protein may have the potential to improve body composition (58) , glucose metabolism (59) and lipid profile (3) . Milk protein and its derived peptides have been shown to reduce blood pressure, possibly via inhibition of angiotensin I-converting enzyme (4,60) .…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Although milk and dairy products are nutrient-rich foods, high-fat milk and dairy products are also a major source of cholesterol-raising SFA, which have been considered to be involved in the pathogenesis of CVD. The currently available evidence, while inconclusive, suggests that high-fat milk and dairy product consumption may not be associated with increased risks of CVD and other cardiometabolic conditions (59,64) . The results from three cohorts of American adults (65) showed that dairy fat was not associated with an increased risk of CVD.…”
Section: Potential Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hidayat et al recently proposed in this journal that milk consumption may prevent type 2 diabetes mellitus (T2DM) especially by enhancement of incretin and insulin responses, consequently leading to lower postprandial glucose levels. Milk's insulinotropic index is three times higher compared with milk's glycemic index.…”
Section: Introductionmentioning
confidence: 99%
“…The insulinotropic protein fraction of milk are the whey proteins (20% of cow milk protein), whereas caseins (80%) enhance serum levels of insulin‐like growth factor‐1 (IGF‐1). In fact, whey ingestion increases the secretion of glucose‐dependent insulinotropic polypeptide (GIP) and enhances insulin responses lowering postprandial glucose levels in healthy individuals and patients with T2DM . The branched‐chain amino acids (BCAAs) leucine, isoleucine, and valine are the major insulinotropic amino acid constituents of whey proteins.…”
Section: Introductionmentioning
confidence: 99%